Doctrine of good faith in contracts : A comparison between conventional and islamic laws - Yusuf Sani, Abubakar; Ahamad Faosiy, Ogunbado; Mpawenimana, Abdallah Saidi (Institute of Medico-Legal Publications, 2018)
The doctrine of good faith is a vital issue amongst the contractual issues of this period .It is considered a main goal of every recognized law of contract system to be promoting good faith as well as fair dealing in forming and performance of contracts. Basically, it has been a common argument in supporting the notion of good faith that it helps in addressing bad faith manner in a clear and direct conduct, allow the law to safeguard the realistic anticipations of women and men as well as encourage a philosophy of contractual collaboration that would lead to economic efficiency. This study looks into the concept of good faith from both the conventional law and Islamic law (Shariah) to find to what extent both laws comply with each other. The study is doctrinal which utilizes descriptive approach of qualitative research methodology which relies on secondary data in form of text books, journals, newspapers, related websites etc. The study found that both the conventional law and Islamic law support the principle of good faith. Shariah recognized the principle of good faith as it asks the parties in a contract to abide by the requirement in various stages of the contract, especially sale contract. Thus, the concept of good faith should have the same application in both Islamic and conventional jurisdictions.